Nano Semiconductors: A Study on Its Importance and Uses: Examining the Value and Applications of Nano Semiconductors (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Semiconductors are characterized by a subordinate energy band gap (Eg), which is the basic energy required to energize an electron from the earliest stage valence energy band into the unfilled energy conductive band. What's more, when the size of semiconductor materials decreases, their physical and substance properties definitely change, resulting in properties due to their enormous region of the surface or effect on the quantum scale. The goal of this study is to explore the value of Nano semiconductors and their use.